Precision Drug Discovery from Zingiber Officinalis: Unraveling Therapeutic Insights for Rheumatoid Arthritis through Innovative In Silico Approaches and Controlled Release Strategies - Ujban Hussain; Samiksha Sandeep Tammewar (Proceedings)
To pioneer an innovative in silico exploration of Zingiber officinalis for Rheumatoid Arthritis, employing virtual screening to discern the impact of its chemical constituents on the cyclo-oxygenase receptor [...]